Occupational exposure to hairdressing chemicals and immunoglobulin E synthesis - Hollund, Bjørg Eli; Moen, Bente Elisabeth; Egeland, Grace M; Florvaag, Erik; Omenaas, Ernst (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'This study assessed the effect of exposure to hairdressing chemicals on total and allergen-specific serum immunoglobulin E (IgE) in hairdressers. ' ' METHODS ': 'The study was based on a questionnaire sent to 100 hairdressers (91% responding) and a reference group of 95 office workers (84% responding). The questionnaire sought information on allergy, respiratory symptoms during the past year, work conditions (exposure), and smoking habits. The hairdressers were divided into two groups, one of high exposure and another of low exposure. Total serum IgE and allergen-specific IgE towards the most prevalent airborne allergens were analyzed. ' ' RESULTS ': 'The serum levels of total IgE were significantly higher among the highly exposed hairdressers than among the office workers. The prevalence of asthma-like respiratory symptoms during the past year was significantly higher among the highly exposed hairdressers than among the office workers. The total serum IgE level was significantly higher among the hairdressers than among the office workers (101 versus 51 IU/ml blood), but this difference disappeared after adjustment for age, atopy, and smoking. A total of 5.5% of the hairdressers versus none of the office workers had specific serum IgE antibodies towards latex. There were no differences in general allergy (Phadiatop(r)) among the hairdressers and office workers. ' ' CONCLUSIONS ': 'Serum levels of total IgE were significantly higher among highly exposed hairdressers than among office workers. The relationship could not be completely explained by such covariables as age, smoking, or sensitization to latex allergens.
Keywords: allergy; hairdressing chemicals; immunoglobulin E synthesis; latex; occupational exposure